9514 1404 393
Answer:
x^2 +4x -21
Step-by-step explanation:
Substitute the given expressions and simplify.
f(x) + g(x)
= (x^2 +3x -28) +(x +7)
= x^2 +(3+1)x +(-28 +7)
= x^2 +4x -21
Answer:
I'm assuming that the s stands for 5 so it would be 19.6
Step-by-step explanation:
Answer:
x = 3
Step-by-step explanation:
4x + 50 + 28 = 90
4x + 78 = 90
4x = 12
x = 3
Answer:
m < 8 = 54.4°
Step-by-step explanation:
Answer:
254 seconds
Step-by-step explanation:
If 1 minute = 60 second
then
60 x 4 = 240 second
then add 14
240 + 14 = 254
Therefore, there are 254 second in 4 minutes and 14 seconds